PENGARUH PEMOTONGAN PAJAK PENGHASILAN (PPh) PASAL 21 TERHADAP GAJI PNS GOLONGAN IV DI DINAS KESEHATAN KOTA BANDUNG - Setiawan, Entang; Triana, Renny (Politeknik Dharma Patria Kebumen, 2017)
The main objective of the research is to analyze the influence of Pemotongan PPh Pasal 21 to the civil servants rank IV salaries at Dinas Kesehatan Bandung. The descriptive method was employed in this research using quantitative approach. The data collection was used in this research was done by observations, interviews, documentations, and completed by literature study. The data which used was withholding PPh Pasal 21 and civil servants rank IV salaries, meanwhile, the technique used to analyze the data were the Pearson product Moment correlation analysis, normality test, coefficient of determination, and linear regression analysis. The result obtained from statistical is found that the increase of withholding income tax was always followed by salaries. The Pearson Product Moment obtained 0,910, bigger than 0,80, which then shows that withholding PPh Pasal 21 significant effect on civil servants rank IV salaries. The coefficient of determination result is 82,80%, it means that income tax cuts of article 21 influenced by civil servants rank IV salaries while the rest 17,2% influenced by other variables that is not described.